Amyloid Precursor Protein Mediates a Tyrosine Kinase-Dependent Activation Response in Endothelial Cells - Austin, Susan A. (Society for Neuroscience, 2009)
Amyloid precursor protein (APP) is a ubiquitously expressed type 1 integral membrane protein. It has the ability to bind numerous extracellular matrix components and propagate signaling responses via its cytoplasmic phospho-tyrosine, (682)YENPTY(687), binding motif. We recently demonstrated increased protein levels of APP, phosphorylated APP (Tyr682), and β-amyloid (Aβ) in brain vasculature of atherosclerotic and Alzheimer's disease (AD) tissue colocalizing primarily within the endothelial layer. This study demonstrates similar APP changes in peripheral vasculature from human and mouse apoE(−/−) aorta, suggesting that APP-related changes are not restricted to brain vasculature. Therefore, primary mouse aortic endothelial cells and human umbilical vein endothelial cells were used as a model system to examine the function of APP in endothelial cells. APP multimerization with an anti-N-terminal APP antibody, 22C11, to simulate ligand binding stimulated an Src kinase family-dependent increase in protein phospho-tyrosine levels, APP phosphorylation, and Aβ secretion. Furthermore, APP multimerization stimulated increased protein levels of the proinflammatory proteins, cyclooxygenase-2 and vascular cell adhesion molecule-1 also in an Src kinase family-dependent manner. Endothelial APP was also involved in mediating monocytic cell adhesion. Collectively, these data demonstrate that endothelial APP regulates immune cell adhesion and stimulates a tyrosine kinase-dependent response driving acquisition of a reactive endothelial phenotype. These APP-mediated events may serve as therapeutic targets for intervention in progressive vascular changes common to cerebrovascular disease and AD.